The effect of cassava (Manihot esculenta) leaf extract on COX-2 expression in the neutrophil cell culture exposed to the lipopolysaccharide of Escherichia coli (in-vitro study) - Meilawaty, Zahara; Dharmayanti, Agustin Wulan Suci; Prafitasari, Dinar (Universitas Padjadjaran, 2019)
Introduction: Neutrophils are cells which played an initial role in the inflammation area and can be induced by lipopolysaccharide (LPS). Activated neutrophils will secrete the COX-2 enzyme which is involved in arachidonic acid synthesis to produce inflammatory mediators. However, excessive inflammation can cause tissue destruction; thus, the body needs anti-inflammation agents. Cassava leaf contains biochemical component which has an anti-inflammation effect. This study was aimed to determine the expression of COX-2 in neutrophils administered with cassava leaf extract and the LPS of E. coli. Methods: This study was experimental laboratories (in vitro study) using human neutrophil cells culture. The samples of this study were divided into 4 groups, administered with 12.5% cassava leaf extract (T1); 25% cassava leaf extract (T2); control group which contained only neutrophils cells (C1); and control group contained neutrophils and LPS (C2). Human neutrophil cells culture was incubated in the 12.5% and 25% cassava leaf extract before exposed with the LPS of E. coli. COX-2 expression was observed with immunochemistry methods. Results: The COX-2 expression in the 12.5% cassava leaf extract group was significantly higher than the 25% cassava leaf extract group (p < 0.05). Conclusion: Cassava leaf extract can inhibit the COX-2 expression and can be used as an alternative anti-inflammation agent.Keywords: Anti-inflammation, cassava leaf extract, COX-2 expression, neutrophils.